Optimizing Visual Quality in Keratoconus: A Review of Recent Advances - Kowalik, Kinga; Michalska, Maria; Zielińska, Aleksandra; Szypulski, Szymon; Skiba, Jakub; Tylczyńska, Kinga; Skiba, Zuzanna; Tylczyńska, Natalia; Iwaniuk, Sebastian; Maciejewski, Ignacy (Quality in Sport, 2025)
Keratoconus (KC) is a progressive, bilateral, and asymmetric corneal disorder that results in corneal thinning and conical protrusion, causing irregular astigmatism and reduced visual acuity. KC prevalence varies widely, with onset typically in the second or third decade and progression stabilizing by the fourth decade. Although the exact etiology remains unclear, genetic and environmental factors, such as family history and eye rubbing, are associated with increased risk, and recent findings suggest inflammatory processes may contribute to pathogenesis. This study aims to evaluate the efficacy of treatment approaches for KC across varying disease stages. Methods include a review of the latest assessment of therapeutic options, from glasses and contact lenses to advanced surgical interventions, including corneal cross-linking and transplantation. Findings indicate that recent advancements in contact lens designs and surgical techniques enhance visual outcomes and slow disease progression. These improvements in KC management provide clinicians with a comprehensive approach for customizing treatment strategies according to disease severity.